Greenhouse gas emissions from a coffee plantation (Coffea arabica) with and without shade of moringa trees (Moringa oleifera) under organic and mineral fertilization in Barva de Heredia - Espinoza Ballestero, Diana (2022)
Greenhouse gas emissions with two fertilization patterns (organic and mineral) with or without shade of Moringa trees (Moringa oleifera) were compared in a coffee plantation (Coffea arabica), Obata variety, in the Santa Lucía Experimental Farm in Barva, Heredia, Costa Rica. The following was conducted for the treatments; T1: with shade and organic fertilization, T2: with shade and mineral fertilization, T3: without shade and organic fertilization, and T4: without shade and mineral fertilization. Emissions were measured for only three different gases: carbon dioxide (CO2), methane (CH4), and nitrate oxide (N2O). Three fertilizations were conducted (mineral and organic) since 2016 and, by 2018 every time there was fertilization, greenhouse gases were sampled using the closed chamber technique for subsequent analysis by chromatography. Gas samples were taken during the three annual fertilizations on days 0, 5, 15, and 30, following application. Sub-samples were extracted from each sample on minute 0, 10, 20, and 30, right after the trap chamber was set. Emissions were also related to climate variables such as temperature, humidity, and precipitation. Different outcomes were obtained for each gas. Gas emissions were lower under shade. Regarding types of fertilization, emissions were higher in organic treatments compared to mineral fertilization. Only carbon dioxide emissions showed correlation with climate factors, registering higher values as temperature increased.